Peran Pembelajaran Pendidikan Pancasila dalam Meningkatkan Kesadaran Bela Negara Siswa Sekolah Dasar - Adini Rahmi; Anggie Ananda Putri; Adrias Adrias; Salmaini Safitri Syam (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
National defense is a concept regulated in a country's legislation, which refers to the patriotic attitude of individuals and groups in the context of citizenship. This study aims to explore the application of the concept of national defense, especially in the context of Pancasila education learning among elementary school students. The research method used in this study is a qualitative method with a literature study approach as a data collection technique. The results of the study indicate that Pancasila education learning has an important role in increasing awareness of national defense among elementary school students. Seeing the low level of public understanding, especially among students, regarding the importance of national defense, prevention efforts can be made by providing education through Pancasila Education subjects. In this lesson, students will be taught about the basic values ​​of national defense, so that the threat of radicalism to the younger generation can be suppressed early on starting from elementary school level. Sustainable national defense can be carried out through education, training, and socialization in schools to strengthen the foundation of the Indonesian State.